Zoom-in Dermoscopy for Facial Tumors - Martina D’Onghia; Francesca Falcinelli; Lorenzo Barbarossa; Alberto Pinto; Alessandra Cartocci; Linda Tognetti; Giovanni Rubegni; Anastasia Batsikosta; Pietro Rubegni; Elisa Cinotti (Diagnostics, 2025)
Background/Objectives: Facial lesions, including lentigo maligna and lentigo maligna melanoma (LM/LMM), both malignant, present significant diagnostic challenges due to their clinical similarity to benign conditions. Although standard dermoscopy is a well-established tool for diagnosis, its inability to reveal cellular-level details highlights the necessity of new magnified techniques. This study aimed to assess the role of standard dermoscopy, high-magnification dermoscopy, and fluorescence-advanced videodermatoscopy (FAV) in diagnosing LM/LMM and differentiating them from benign facial lesions. Methods: This retrospective, observational, multicenter study evaluated 85 patients with facial skin lesions (including LM, LMM, basal-cell carcinoma, solar lentigo, seborrheic keratosis, actinic keratosis, and nevi) who underwent dermatological examination for skin tumor screening. Standard dermoscopy at 30× magnification (D30), high-magnification dermoscopy at 150× magnification (D150), and FAV examination were performed. Dermoscopic images were retrospectively evaluated for the presence of fifteen 30× and twenty-one 150× dermoscopic features, and their frequency was calculated. To compare D30 with D150 and D150 with FAV, the Gwet AC1 concordance index and the correct classification rate (CCR) were estimated. Results: Among 85 facial lesions analyzed, LM/LMM exhibited distinctive dermoscopic features at D30, including a blue–white veil (38.9% vs. 1.7%, p < 0.001), regression structures (55.6% vs. 21.7%, p = 0.013), irregular dots or globules (50.0% vs. 10%, p = 0.001), angulated lines (72.2% vs. 6.7%, p < 0.001), an annular granular pattern (61.1% vs. 20%, p = 0.002), asymmetrical pigmented follicular openings (100.0% vs. 21.7%; p < 0.001), and follicular obliteration (27.8% vs. 3.3%). At D150, roundish melanocytes (87.5% vs. 18.2%, p < 0.001) and melanophages (43.8% vs. 14.5%, p = 0.019) were predominant. FAV examination identified large dendritic cells, isolated melanocytes, and free melanin in LM/LMM (all p < 0.001) with high concordance to D150. Conclusions: Integrating D30, D150, and FAV into clinical practice may enhance diagnostic precision for facial lesions by combining macroscopic and cellular insights, thereby reducing unnecessary biopsies. However, future studies are essential to confirm these results.